2014
DOI: 10.1042/bj20140587
|View full text |Cite
|
Sign up to set email alerts
|

The structure of the Slrp–Trx1 complex sheds light on the autoinhibition mechanism of the type III secretion system effectors of the NEL family

Abstract: Salmonella infections are a leading cause of bacterial foodborne illness in the United States and the European Union. Antimicrobial therapy is often administered to treat the infection but increasing isolates are being detected that demonstrate resistance to multiple antibiotics. Salmonella enterica contains two virulence related type-III secretion systems (T3SS): one promotes invasion of the intestine and the other one mediates systemic disease. Both of them secrete the SlrP protein acting as E3 ubiquitin lig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 48 publications
1
32
0
Order By: Relevance
“…Much of the recent literature on SspH/IpaH E3s has focused on the large reorientation of the LRR and E3 domains observed in various crystal structures (16,19,21,32). Our further analysis of the same structures revealed that the E3 domains themselves can also adopt multiple conformations.…”
Section: Ssph1 Uses a Modular And Dynamic E3 Domain For Ub Transfermentioning
confidence: 64%
See 2 more Smart Citations
“…Much of the recent literature on SspH/IpaH E3s has focused on the large reorientation of the LRR and E3 domains observed in various crystal structures (16,19,21,32). Our further analysis of the same structures revealed that the E3 domains themselves can also adopt multiple conformations.…”
Section: Ssph1 Uses a Modular And Dynamic E3 Domain For Ub Transfermentioning
confidence: 64%
“…1B). Subsequent structures all exhibit the same overall ␣-helical fold (12)(13)(14)21). Despite this similarity, close inspection reveals conformational heterogeneity within the E3 domain.…”
Section: Ssph/ipah E3 Domains Can Be Divided Into Two Distinct Subdommentioning
confidence: 93%
See 1 more Smart Citation
“…The E3 ubiquitin ligase SlrP is translocated both via SPI‐1‐ and SPI‐2‐encoded T3SS (Cordero‐Alba & Ramos‐Morales, ; Ellermeier & Slauch, ). The host reduction/oxidation‐regulatory protein thioredoxin‐1 (Trx1) was identified to undergo SlrP‐mediated ubiquitinylation, which results, through a proteolytic or a nonproteolytic pathway, in decreased activity of Trx1 and an increase in host cell death (Bernal‐Bayard & Ramos‐Morales, ; Zouhir et al, ). Additionally, SlrP interacts with ERdj3 thereby interfering with the function of the host endoplasmic reticulum lumenal chaperone.…”
Section: Introductionmentioning
confidence: 99%
“…The LRR domain is connected to the NEL domain through a flexible linker and inhibits its ubiquitin ligase activity in the absence of substrate proteins (Chou et al, 2012;Quezada et al, 2009;Keszei and Sicheri, 2017). Removal of the LRR domain from SspH1, SspH2, SlrP or IpaH9.8 increases their E3 ligase activity (Quezada et al, 2009;Chou et al, 2012;Zouhir et al, 2014). A structural study of SspH1 showed that the binding of the host protein kinase N1 (PKN1) to the LRR domain releases its inhibitory effect on the NEL domain, which promotes the ubiquitylation and degradation of PKN1, and leads to the attenuation of the androgen response (Haraga and Miller, 2006;Keszei et al, 2014).…”
Section: Novel E3 Ligasesmentioning
confidence: 99%